ABUNDANCE AND DIVERSITY OF ROTIFERA IN THE GARMAT ALI REGION PONDS, BASRAH-IRAQ. - ABDULHUSSEIN H. GHAZI; AHMED, HUDA K. (Iraqi Journal of Aquaculture, 2022)
The study is based on Samples of Rotifera collected from three ponds located inside the University campus, Garmat Ali region Basrah, Iraq. The samples were investigated for the density changes and for the diversity. There were found 26 species of Rotifera belong to 20 genera. The maximum recorded density was (51 ind. / l) which observed in May/2006 at pond 1, whereas the minimum density was (0.6 ind / l) recorded at pond 1 in November/2006. The total density was (225 ind. / l) at pond 1. It was found that the diversity of Rotifera (no. of spp.) is greater at pond 2 and pond 3 compared with pond 1. There were 22 species at pond 2 and pond 3 but only 9 species at pond 1.